Virtual Reality-Based Learning Environments for Enhancing Interpersonal Communication and Decision Making in Crisis Management Training - Mustaqim; Fakhriyah, Fina (Generate Digital Publishing, 2024)
Objective: This research explores the potential of Virtual Reality (VR) in crisis management training, with a particular focus on improving soft skills such as communication, empathy, and decision-making. Research Design & Methods: This research utilizes a systematic literature review of studies examining VR-based crisis management training. Key findings from empirical studies were analyzed to understand the role of VR in simulating realistic crisis scenarios and its impact on technical and soft skills development. Findings: VR-based training shows significant potential in improving soft skills, including communication, teamwork, and decision-making under pressure. Programs such as PANDORA and JUST VR show effective results when soft skills are intentionally integrated into training modules. However, accessibility and cost barriers remain significant, and many existing programs focus more on technical skills, often neglecting the soft skills component. Implications & Recommendations: To maximize the potential of VR in crisis management training, integration of soft skills should be a priority throughout the program, with collaboration between technology developers, educators, and practitioners. Further research needs to explore innovative, affordable VR training models and measure their impact on real-world crisis performance. Contribution & Value Added: This research expands knowledge about the role of VR in crisis management education, emphasizing opportunities and challenges in integrating soft skills. The results offer a roadmap for developing more comprehensive and accessible crisis training programs, to produce professionals capable of dealing with complex and stressful situations.